Analisis pelaksanaan half day school terhadap interaksi sosial anak di lingkungan sekolah smp it asy syadzili sumberpasir - sobih, muhammad (Maliki Interdisciplinary Journal, 2026)
English abstract. Education is not solely oriented toward academic achievement but also plays a crucial role in shaping students’ character and social interaction skills. One educational model that has developed in Indonesia is the half-day school system, which is considered capable of balancing academic learning, character development, and students’ social lives. This study aims to describe the implementation of the half-day school system, analyze students’ social interactions, and examine the effects of half-day school implementation on the quality of students’ social interactions at SMP IT Asy-Syadzili Sumberpasir, a pesantren-based junior high school. This study employed a qualitative research approach, with data collected through observation, interviews, and documentation.The findings indicate that the half-day school system at SMP IT Asy-Syadzili Sumberpasir is closely integrated with pesantren activities, creating a balance between academic instruction and spiritual development. The implementation of this system has a positive impact on the quality of students’ social interactions with peers, teachers, and pesantren administrators. Students demonstrate higher levels of communication skills, cooperation, discipline, empathy, and social responsibility. Moreover, the shorter duration of formal schooling allows students to maintain meaningful interactions with their families, which further supports their personal and social development. Therefore, the pesantren-based half-day school system is not only effective in supporting formal education but also contributes significantly to the development of students’ character and social competence.